Respon Morfologis dan Fisiologis Beberapa Varietas Kedelai (Glycine max L. Merrill) di Tanah Masam - Anna Eka; Diana Sofia Hanafiah; Isman Nuriadi (Jurnal Agroekoteknologi, 2015)
The aim of the research was to determine the morphological and physiological response of severalsoybean varieties in acid soil. This research was conducted at the screen house at Faculty ofAgriculture, University of North Sumatra-Medan (± 25 m asl) from April-August 2014, using arandomized block design with 2 factors ie varieties (Tanggamus, Detam 2, Anjasmoro and Detam1) and media (liming and addition of sulfur). The parameters measured were plant height, rootlength, number of branches, leaf area, days of flowering, the amount of chlorophyll a and b,harvesting age, number of pods per sample, number of containing pods per sample. The resultsshowed that the varieties significantly different the parameters of leaf area, days to flowering,harvesting age, number of pods per sample and the number of containing pods per sample. Themedia had no significant effect on all parameters were observed.Keywords:soybean variety, liming, acidsoil